KAJIAN PRODUKSI MINUMAN CAMPURAN SARI WORTEL DENGAN BERBAGAI BUAH - Triastuti, Ikrar; Nurainy, Fibra; Nawansih, Otik (Jurnal Teknologi & Industri Hasil Pertanian, 2013)
This research was aimed to find the most preferred fruit  to be mixed with carrot juice, to determine the formulation of carrot and the chosen fruit that give  the best mixed juice, and to elucidate the physical and chemical characteristics of the chosen juice  stored at 10°C for 6 days. The fruits to be chosen were pineapple, orange, red guava, mango, passion fruit. The formulations carrot and the chosen fruit used were 50%: 50%, 60%: 40%, 70%: 30%, 80%: 20%, 90%, 10%, and 100%: 0%. The results showed that the most preferred fruit to be mixed with carrot  was soursop. Selected formula that gave the best sensory properties was 80% carrot : 20% soursop.  This mixed juice  had scores for aroma, taste, color, and overall acceptance of 3 (like slightly), 3.600 (like), and 3.240 (like slightly) . During  6- days of cold storage there was a slight decrease in vitamin C, total soluble solid, and cloud stability, but there was a slight increase in pH. Keywords: carrot, cloud stability, mixed juice, soursoup